Synthesis, structural and morphological characterization of CeO2 – ZnO nanosized powder systems from Pechini’s method - Peverari, Cinara; Pires, Ana Maria; Gonçalves, Rogéria Rocha; Serra, Osvaldo Antonio (Eclética Química, 2005)
This work reports on the investigation of nanosized CeO 2 -ZnO systems prepared by Pechini's method. The structural and morphological characterization of CeO 2 -ZnO systems as well as the characterization of CeO 2 and ZnO separately, showed that the employed method result in powders with spheroidal particles whose size are in the range 30 - 200 nm, which is appropriate to provide homogeneous suspensions. The ZnO present in the prepared mixed oxides seems to increase particle size distribution and to influence the arrangement of the particles after powder dispersion.